SYNTHESIS, ANTIMICROBIAL AND ANTI-INFLAMMATORY ACTIVITY OF NEWLY SYNTHESIZED ISOXAZOLINE INCORPORATED 2-QUINOLONES (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
A series of novel substituted 1-amino-3-(5-phenyl-4,5-dihydroisoxazol-3-yl) quinolin-2(1H)-one (AJI1-AJI8) have been synthesized upon reaction with 1-amino-3-cinnamoyl-quinolin-2(1H)-one by using hydroxylamine hydrochloride as cyclising agent in alcohol medium. The intermediate chalcones 1-amino-3-cinnamoyl-quinolin-2(1H)-one (AJC1-AJC8) were synthesized by condensing 3-acetyl-1-amino-quinolin-2-one with different substituted benzaldehyde in presence of 40% ethanolic KOH. The title compounds obtained were characterized by IR, 1H NMR, mass spectra and elemental analysis. The synthesized compounds were screened for their antimicrobial and anti-inflammatory activity.